2015
DOI: 10.1063/1.4922371
|View full text |Cite
|
Sign up to set email alerts
|

Plasma absorption evidence via chirped pulse spectral transmission measurements

Abstract: This work aims at highlighting the plasma generation dynamics and absorption when a Bessel beam propagates in glass. We developed a simple diagnostics allowing us to retrieve clear indications of the formation of the plasma in the material, thanks to transmission measurements in the angular and wavelength domains. This technique featured by the use of a single chirped pulse having the role of pump and probe simultaneously leads to results showing the plasma nonlinear absorption effect on the trailing part of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Pulsed lasers based on Bessel beams are widely used in micro-and nanofabrication of hard and brittle materials, such as surface microstructuring [17,18], drilling, and microchannel fabrication [19][20][21][22][23]. Relevant studies have confirmed the positive impact of laser spatiotemporal shaping on the processing of glass materials [24][25][26][27][28][29]. The work of several scholars has shown that the processing parameters related to spot spacing, laser incident power, and burst mode have a significant effect on the processing quality of the samples [30][31][32][33][34][35].…”
Section: Introductionmentioning
confidence: 99%
“…Pulsed lasers based on Bessel beams are widely used in micro-and nanofabrication of hard and brittle materials, such as surface microstructuring [17,18], drilling, and microchannel fabrication [19][20][21][22][23]. Relevant studies have confirmed the positive impact of laser spatiotemporal shaping on the processing of glass materials [24][25][26][27][28][29]. The work of several scholars has shown that the processing parameters related to spot spacing, laser incident power, and burst mode have a significant effect on the processing quality of the samples [30][31][32][33][34][35].…”
Section: Introductionmentioning
confidence: 99%